Responsive biomimetic networks from polyisocyanopeptide hydrogels - Kouwer, Paul H. J.; Koepf, Matthieu; Le Sage, Vincent A. A.; Jaspers, Maarten; van Buul, Arend M.; Eksteen-Akeroyd, Zaskia H.; Woltinge, Tim; Schwartz, Erik; Kitto, Heather J.; Hoogenboom, Richard; Picken, Stephen J.; Nolte, Roeland J. M.; et al. (Nature (London), 2013)
Thermal transitions of polyisocyanide single molecules to polymer bundles and finally networks lead to hydrogels mimicking the properties of biopolymer intermediate-filament networks; their analysis shows that bundling and chain stiffness are crucial design parameters for hydrogels. Biomimetic polymer networks This paper describes a new class of water-soluble, relatively stiff polymers that bundle in a controlled manner on heating to produce very stiff fibres. These fibres, in turn, form hydrogels that very closely mimic components of the cell cytoskeleton, intermediate filaments. Synthesis involves the thermal transition of polyisocyanide polymers from single molecules to bundles of polymer chains. Networks made with this material demonstrate a stress-stiffening behaviour that is usually absent in synthetic polymer gels, and their mechanical properties can be modified by altering the chemical structure of the polymer, offering greater versatility than biopolymer networks. Mechanical responsiveness is essential to all biological systems down to the level of tissues and cells 1 , 2 . The intra- and extracellular mechanics of such systems are governed by a series of proteins, such as microtubules, actin, intermediate filaments and collagen 3 , 4 . As a general design motif, these proteins self-assemble into helical structures and superstructures that differ in diameter and persistence length to cover the full mechanical spectrum 1 . Gels of cytoskeletal proteins display particular mechanical responses (stress stiffening) that until now have been absent in synthetic polymeric and low-molar-mass gels. Here we present synthetic gels that mimic in nearly all aspects gels prepared from intermediate filaments. They are prepared from polyisocyanopeptides 5 , 6 , 7 grafted with oligo(ethylene glycol) side chains. These responsive polymers possess a stiff and helical architecture, and show a tunable thermal transition where the chains bundle together to generate transparent gels at extremely low concentrations. Using characterization techniques operating at different length scales (for example, macroscopic rheology, atomic force microscopy and molecular force spectroscopy) combined with an appropriate theoretical network model 8 , 9 , 10 , we establish the hierarchical relationship between the bulk mechanical properties and the single-molecule parameters. Our results show that to develop artificial cytoskeletal or extracellular matrix mimics, the essential design parameters are not only the molecular stiffness, but also the extent of bundling. In contrast to the peptidic materials, our polyisocyanide polymers are readily modified, giving a starting point for functional biomimetic hydrogels with potentially a wide variety of applications 11 , 12 , 13 , 14 , in particular in the biomedical field.